479 Penetrating Chest Trauma Causing A Superior Mesenteric Artery-Inferior Vena Cava Fistula and Pancreatic Injury: A Case Report. (12th October 2021) - Wagner, K; Reimann, S; Budge, M; Claydon, M; Musicki, K; Ban, E.-Jun
Abstract: Penetrating traumatic injuries can present a challenging scenario due to the potential for multisystem involvement requiring swift collaboration between surgical specialities. We present the case of a 66-year-old female who was stabbed in the right posterior chest. CT revealed a diaphragmatic injury, liver laceration involving segments 6/7 with active bleeding, and a posterior superior mesenteric artery (SMA) to anterior inferior vena cava (IVC) fistula. Due to the proximity of the SMA injury to a replaced right hepatic artery origin, the fistulous connection with the suprarenal IVC, and suspected pancreatic and duodenal injuries, a hybrid rather than a purely endovascular approach was taken. A large compliant occlusion balloon was placed percutaneously in the hepatic IVC. Subsequent trauma laparotomy and right medial visceral rotation identified SMA and SMV injuries, which were repaired with temporary supracoeliac aortic clamping. Further kocherisation of the duodenum revealed a 10 cm longitudinal IVC laceration causing sudden large volume venous haemorrhage. This was repaired after control was gained with supracoeliac aortic clamping, infrarenal IVC vessel loop and balloon inflation. An abdominal VAC dressing was applied. Before transfer to ICU, however, 1L of blood was noted in the VAC cannister and a relook laparotomy demonstrated more than 1L of intrabdominal fresh blood. Bleeding vessels around the uncinate process were ligated. After 48 hours, a relook laparotomy revealed no significant bleeding, and the abdomen was closed. A post-operative MRCP demonstrated pancreatic divisum and likely laceration of the aberrant ventral duct. A subsequent peripancreatic collection was managed conservatively.